2013
DOI: 10.1155/2013/548690
|View full text |Cite
|
Sign up to set email alerts
|

New Lax Pairs and Darboux Transformation and Its Application to a Shallow Water Wave Model of Generalized KdV Type

Abstract: New Lax pairs of a shallow water wave model of generalized KdV equation type are presented. According to this Lax pair, we constructed a new spectral problem. By using this spectral problem, we constructed Darboux transformation with the help of a gauge transformation. Applying this Darboux transformation, some new exact solutions including double-soliton solution of the shallow water wave model of generalized KdV equation type are obtained. In order to visually show dynamical behaviors of these double soliton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, the exact closed-form solutions of these equations play a fundamental role in unraveling the dynamic and help to understand/comprehend the mechanism of the existent state. A variety of novel approaches have been effectively utilized, developed, and improved by collections of assorted researchers for retrieving the exact solutions of NLEEs where the most important goes back to Lax pair [1], bifurcation method [2,3], extended mapping method [4], the tanh method [5], extended multiple Riccati equations expansion method [6], inverse scattering method [7], extended Jacobian elliptic function expansion method [8,9], Lie symmetry analysis [10][11][12][13][14][15][16], generalized Kudryashov method [17], etc. Although there is no particular universal technique that is applicable to all NLPDEs.…”
Section: Aims and Scopementioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the exact closed-form solutions of these equations play a fundamental role in unraveling the dynamic and help to understand/comprehend the mechanism of the existent state. A variety of novel approaches have been effectively utilized, developed, and improved by collections of assorted researchers for retrieving the exact solutions of NLEEs where the most important goes back to Lax pair [1], bifurcation method [2,3], extended mapping method [4], the tanh method [5], extended multiple Riccati equations expansion method [6], inverse scattering method [7], extended Jacobian elliptic function expansion method [8,9], Lie symmetry analysis [10][11][12][13][14][15][16], generalized Kudryashov method [17], etc. Although there is no particular universal technique that is applicable to all NLPDEs.…”
Section: Aims and Scopementioning
confidence: 99%
“…was introduced by Sakovich in [18]. It was observed that equation (1) which is quadratic in u xx is Painlevé integrable and gives soliton solutions of KdV-type. The KdV equation which is known as Korteweg-de Vries…”
Section: A Brief Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The Lax pairs of (2) were given by Fokas in [40]. New Lax pairs and Darboux transformation of (2) were introduced by Yang and Rui in [43] recently. In [44], by using the bifurcation theory of dynamical system, the existence conditions of different kinds of traveling wave solutions of (2) were presented by Bi.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%